2016
DOI: 10.2460/javma.249.12.1428
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of serum cardiac troponin I concentration as a marker of survival of harbor seal (Phoca vitulina) pups during rehabilitation

Abstract: OBJECTIVE To measure serum cardiac troponin I (cTnI) concentrations in orphaned harbor seal (Phoca vitulina) pups at various points during rehabilitation in a seal rescue center and determine whether cTnI concentration was associated with survival during rehabilitation and duration of rehabilitation. DESIGN Serial cross-sectional study. ANIMALS Fifty-five 2- to 9-day-old harbor seal pups. PROCEDURES Blood samples for serum cTnI concentration measurement, CBC, and serum biochemical analysis were obtained from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
2
4
1
Order By: Relevance
“…Our hematological values were also comparable to other reported values for harbor seal pups in rehabilitation (Fonfara et al, 2016; Frouin et al, 2013; Greig et al, 2010; Lander et al, 2003; Morgan et al, 2009; Witte et al, 2014), and again we found strong relationships with survival in contrast to much previous research. Specifically, lower survival was associated with values below the reference range for WBC counts, neutrophils, lymphocytes, and platelets.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our hematological values were also comparable to other reported values for harbor seal pups in rehabilitation (Fonfara et al, 2016; Frouin et al, 2013; Greig et al, 2010; Lander et al, 2003; Morgan et al, 2009; Witte et al, 2014), and again we found strong relationships with survival in contrast to much previous research. Specifically, lower survival was associated with values below the reference range for WBC counts, neutrophils, lymphocytes, and platelets.…”
Section: Discussionsupporting
confidence: 91%
“…In free‐ranging harbor seals, lactation lasts only 24 to 32 days (Cottrell et al, 2002; Muelbert & Bowen, 1993) and preweaning mortality ranges from 3% to 31%, with most deaths occurring in the first two weeks (Hastings et al, 2012; Huggins et al, 2013; Steiger et al, 1989). Prerelease mortality rates for pups in rehabilitation vary from 7% to 76% (Dierauf et al, 1986; Fonfara et al, 2016; Frouin et al, 2013; Greig et al, 2010; MacRae et al, 2011; Witte et al, 2014), with most deaths also occurring within approximately 20 days of their estimated birth (Greig et al, 2010; Witte et al, 2014). Thus, both free‐ranging and rehabilitated harbor seal pups appear to be vulnerable during the early preweaning period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harbor seal (Phoca vitulina) pups that die during or after rehabilitation have been found to have a significantly higher antemortem serum cTnI concentration at admission than do those that survive after release. 42 Although this was not the aim of the present study, we observed that healthy managed sea otters with the highest cTnI values were those with unsuccessful releases into the wild. One died of emaciation 2 weeks after release.…”
Section: Discussionmentioning
confidence: 55%
“…39 Regardless of etiology, myocardial damage and a high serum cTnI concentration have been associated with an increased risk of death in the short and long term in various species, emphasizing the utility of serum cTnI concentration as a prognostic indicator. 16,19,33,[40][41][42] This clinical tool may be particularly useful in wildlife rehabilitation. Harbor seal (Phoca vitulina) pups that die during or after rehabilitation have been found to have a significantly higher antemortem serum cTnI concentration at admission than do those that survive after release.…”
Section: Discussionmentioning
confidence: 99%